The Effect Of Cadmium on Sperm Quality and Fertilization Of Cyprinus carpio L. - Alfiah Hayati; Khusnita Giarti; Yuli Winarsih; Muhammad Hilman Fuadil Amin (Universitas Gadjah Mada, 2017)
The objective of the study was to determine the effect of cadmium on sperm quality and fertilization of C. carpio L. Sperm and eggs were collected by abdomen striping from the mature testis and ovary of C. carpio L. This study used one control and four treatment groups of variation on the cadmium concentration (0, 50, 100, 150, and 200 ppm) with eight replications. Sperm motility (mass motility, mass motility duration, and individual motility duration) and viability were measured after three to four seconds of incubation in the water. The percentage of fertility success was calculated by observing embryo development after the eggs were mixed with sperm and incubated in the water for 72 hours. The success of the fertilization process was indicated by a color change of the egg that darkens after successful fertilization, and white-milk if failed. The data were analyzed using analysis of variance (α = 0.05). The results of this study indicate that exposure of 50 ppm cadmium and control group shown success in term of sperm quality (motility and viability) and fertilization, but at 100 ppm or more decreased the sperm quality and fertilization rate. It can be concluded that cadmium exposure decreases sperm quality and fertility at 100 ppm or higher concentrations.